Parallel texts interviews and interventions about art - Burgin, Victor (Reaktion Books, 2011)
Parallel Texts follows the movement of Burgin's ideas from the late 1960s, when he was an originator of Conceptual Art, through to his most recent discussions of the relationship of art to personal experience, mass media and politics in an early 21st century world transformed by cultural and economic globalization and digital technologies. The book offers an introduction to Burgin's work, also to the evolving artistic and intellectual history in which it was produced, for all interested in contemporary art and art theory.--Back cover